2011
DOI: 10.1111/j.1463-1326.2011.01366.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of LY2189265, a long-acting glucagon-like peptide-1 analogue, in a randomized, placebo-controlled, double-blind study of overweight/obese patients with type 2 diabetes: the EGO study

Abstract: LY2189265, given to overweight/obese patients with type 2 diabetes for 16 weeks in combination with OAMs, was relatively well tolerated and significantly reduced A1c, blood glucose and body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 26 publications
8
100
1
1
Order By: Relevance
“…In this population, patients receiving dulaglutide 1.5 mg achieved a further 1.5% HbA 1c reduction from the baseline mean HbA 1c of 8.1% (65 mmol/mol), with 78% achieving the goal of ,7.0% (53 mmol/mol); both results are superior to exenatide. The previously reported similar glycemic effect of dulaglutide (12) and exenatide (13,14) compared with placebo provides additional support for the current results.…”
Section: Discussionsupporting
confidence: 78%
“…In this population, patients receiving dulaglutide 1.5 mg achieved a further 1.5% HbA 1c reduction from the baseline mean HbA 1c of 8.1% (65 mmol/mol), with 78% achieving the goal of ,7.0% (53 mmol/mol); both results are superior to exenatide. The previously reported similar glycemic effect of dulaglutide (12) and exenatide (13,14) compared with placebo provides additional support for the current results.…”
Section: Discussionsupporting
confidence: 78%
“…Dulaglutide exhibits GLP-1-mediated effects, including glucose-dependent potentiation of insulin secretion, inhibition of glucagon secretion, delay of gastric emptying, and weight loss. In phase 2 studies, dulaglutide demonstrated significant dose-dependent improvements in glycemic control and body weight and a low rate of hypoglycemia (10,11). The most frequent side effects of dulaglutide in these studies were GI related, as observed with other GLP-1 receptor agonists (10)(11)(12).…”
mentioning
confidence: 89%
“…In one randomized, multicenter, double-blind, parallel-group study, the incidence of GI AEs in subjects receiving albiglutide 30 mg weekly was less (29.0%) than that observed for the highest biweekly (54.3%) and monthly doses (55.9%) of albiglutide or exenatide [46]. In a randomized, placebo-controlled, double-blind study of overweight patients with T2DM, nausea occurred in 13.6% of those in the dulaglutide group compared with 7.6% in the placebo group [47]. One study examining the US FDA database of reported AEs from 2004 to 2009 found evidence of increased risk of pancreatitis with exenatide and cautioned about long-term use [48].…”
Section: Safety Of Long-acting Glp-1rasmentioning
confidence: 99%